Analysis of The Influence of Motivation And Spiritual Capital on Performance With Competence as A Moderating Variable In MSMES Community of Kwala Serapuh Langkat - M. Chaerul Rizky; Annisa Ilmi Faried; Echa Ferina Br. Purba (Penerbit Jurnal Indonesia, 2024)
This study aims to analyze the influence of motivation and spiritual capital on the performance of MSMEs in Kwala Serapuh Langkat Village, with competence as a moderating variable. Motivation and spiritual capital are seen as important factors that can affect the performance of MSMEs, while competence plays a role as a moderating variable that can strengthen or weaken this influence. The research method used is a quantitative approach by distributing questionnaires to MSME actors in Kwala Village, Serapuh Langkat. The data obtained were analyzed using multiple regression analysis and Moderated Regression Analysis (MRA) with the help of SmartPLS 2. software to test the effect of competency moderation on the relationship between motivation, spiritual capital, and MSME performance. The results of the study show that motivation and spiritual capital have a positive and significant influence on the performance of MSMEs in Kwala Village, Serapuh Langkat. In addition, competence has not been proven to moderate the influence of motivation and spiritual capital on the performance of MSMEs.